Reference data on hand grip and lower limb strength using the Nintendo Wii balance board: a cross-sectional study of 354 subjects from 20 to 99 years of age - Eika, F.; Blomkvist, A. W.; Rahbek, M. T.; Eikhof, K. D.; Hansen, M. D.; Søndergaard, M.; Ryg, J.; Andersen, S.; Jorgensen, M. G. (BMC musculoskeletal disorders, 2019)
Accurate assessment of isometric hand grip strength (HGS) and isometric lower limb strength (LS) are often limited to specialized clinics due to high costs and need for specialized equipment and personnel. A mobile and user-friendly device would facilitate a wider use of these measures in the clinical setting. The Nintendo Wii Balance Board (WBB) is a novel and pragmatic tool that has been validated for measuring muscle strength and other clinically relevant physiological variables. However, reference data for HGS and LS are lacking. The purpose of the current study is to establish reference data for HGS and LS in individuals ≥20 years of age using the WBB method, and to characterize the effects of age in these measurements. Healthy participants were recruited at various locations and their HGS and LS were tested by six assessors using the WBB. Reference data were analysed and presented in age-groups, while the age-related change in HGS and LS was tested and characterized with linear regression models. Three hundred and fifty-four participants between 20 and 99 years of age were tested. Data are presented separately according to gender and the following age categories: 20-29, 30-39, 40-49, 50-59, 60-69, 70-79, and 80+, and presented in absolute values as well as percentiles. The main findings were; (1) Significantly higher HGS and LS among males compared to females and for the dominant limb compared to the non-dominant limb, (2) a significant decline in strength with increasing age, and (3) the rate of decline increased significantly (i.e. it was non-linear) with age for HGS, but not for LS. This study reported reference data with percentiles for a novel method for assessing HGS and LS. Data were consistent with previously known effects of age and gender on HGS and LS. The presented data may supplement future trials using the WBB in research or in the clinical setting.